The impact of interaction with children on internet addiction in older adults: A moderated mediation model - Yang, Yang; Liu, Tianyuan; Jia, Yu (Frontiers in Psychology, 2022)
Internet addiction among older adults is a new problem in many countries. However, previous studies on excessive Internet use have focused more on young people, and only few studies have focused on Internet addiction in older adults. There is a need to continue to expand research on Internet addiction in older adults. This paper aimed to fill the gap in exiting literature. We adopted a self-reported questionnaire to assess the elderly’s interaction with children, loneliness, life satisfaction and Internet addiction among old adults. A total of 241 old people were obtained from data collection in China via online survey with the help of a professional research company. We used OLS regression analysis and bootstrap method to test the hypothesis. The results of the empirical analysis indicated that 1) interaction with children was significantly negatively associated with the Internet addiction of old people; 2) loneliness mediated the relationship between interaction with children and old adults’ Internet addiction; and 3) life satisfaction moderated the effect of interaction with children, and the indirect effect between interaction with children and old adults’ addiction via loneliness was stronger for those with low life satisfaction. Finally, we discussed the theoretical significance, practical implications, limitation of this research. Interventions to improve family function systems, especially for older people with low life satisfaction can help prevent the development of Internet addiction.